Experimental Investigation of Heat-Damaged RC Slender Spiral Columns Repaired with CFRP Rope - Ahmed M. Ashteyat; Ala’ Taleb Obaidat (Infrastructures)
Carbon fiber-reinforced polymer (CFRP) is widely used in construction to extend the service life of building structures through the repair and rehabilitation of reinforced concrete (RC) columns. However, due to the difficulty of wrapping CFRP strips spirally around an RC spiral column, a flexible CFRP rope material has been developed as an alternative, which will be used as a spiral hoop for repairing circular columns. In this study, 12 RC spiral columns were constructed and tested under concentric load, considering slenderness ratio and spacing between CFRP rope and heat temperature, to investigate the RC spiral column’s behavior. These RC columns had three slenderness ratios with 17.75, 26.65, and 33.34 and were exposed to heat temperature of 600 °C for 3 h, then tested under compression. The results showed that as the slenderness ratio increases, the load capacity of RC spiral column decreases. The repaired specimens with a CFRP rope-with-slenderness ratio of 33.35 and 26.65 exhibited an increase in strength about (36% to 97%) and (30% to 88%), respectively. In all repaired specimens with a CFRP rope-of-slenderness ratio of 26.65 and 33.35, they showed a slight increase in ductility of about 2% compared with the heated specimen. However, they did not recover the ductility of the unheated specimen. Also, the specimens with a low slenderness ratio and repaired with CFRP at 300 mm showed a greater decrease in toughness and modulus of elasticity than in the specimens with a high slenderness ratio and repaired with CFRP at 150 mm. The repaired specimens with rope at 150 mm of spacing exhibited an increase in load capacity more than the repaired specimen with rope at 300 mm of spacing and reached a load capacity that was greater than what the unheated specimen reached in all groups. It can be shown that there is a significant effect of temperature on the behaviour of the RC spiral column. Adding rope at 300 mm of spacing restores the capacity and allows for a greater reach than the unheated load capacity of the specimens (about 4% to 11%). However, the specimens repaired with rope at 150 mm increased the load capacity by approximately 27.4% to 36.8% more than the unheated specimens in each group.